2001
DOI: 10.1046/j.1365-2141.2001.02801.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukaemia M0: haematological, immunophenotypic and cytogenetic characteristics and their prognostic significance: an analysis in 241 patients

Abstract: Summary. Haematological, immunophenotypic and cytogenetic characteristics were analysed in 241 patients with acute myeloid leukaemia (AML) M0, including 58 children. Children , 3 years and adults between 60 and 70 years of age were most frequently affected. Immunophenotyping showed a heterogeneous phenotype. Anti-myeloperoxidase was positive in about half of the patients. Cytogenetic data were available from 129 (54%) patients. A normal karyotype was found in only 24%. Most of the abnormalities were unbalanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 38 publications
4
29
0
Order By: Relevance
“…In contrast, PML-RARA and NPM1 mutations had a higher frequency in the in the AML-ma group. These results are supported by previous studies, in which AML FAB M0 was associated an accumulation the same adverse chromosomal aberrations, a higher age and consequently a worse outcome [18][19][20]. Furthermore, also in recently published studies, a lower frequency of favorable molecular aberrations such as NPM1 and CEBPA has been described in the more immature AML subgroup AML FAB M0 [21].…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, PML-RARA and NPM1 mutations had a higher frequency in the in the AML-ma group. These results are supported by previous studies, in which AML FAB M0 was associated an accumulation the same adverse chromosomal aberrations, a higher age and consequently a worse outcome [18][19][20]. Furthermore, also in recently published studies, a lower frequency of favorable molecular aberrations such as NPM1 and CEBPA has been described in the more immature AML subgroup AML FAB M0 [21].…”
Section: Discussionsupporting
confidence: 87%
“…The prognostic value of CD14 expression was independent of the FAB classification in the MD subset and had already been reported in such FAB subsets as M3 (22) or M0. (2) The imbalanced prognostic weight of CD7,-CD14, or CD34 expression in different immunological settings could explain the discrepancies previously observed when analyzing individually the prognostic value of these antigens expression. (19-21, 24-28, 30-39) The relation between the proposed immunological classification of AML and cytogenetic subsets remain to be determined.…”
Section: Discussionmentioning
confidence: 46%
“…The distance linkage between CD7 and the cluster CD13/ CD33/CD117 was larger than that observed between CD34 and the pan-myeloid antigens. Moreover, the frequency of CD7 expression decreased along granulomonocytic AML maturation from MB to ME (2), while the frequency of CD34 positivity was quite similar in all these AML subsets. This indicates that, as in normal myeloid differentiation, (15,16) CD7 is likely to be expressed in a small compartment of immature cells, while CD34 is expressed on a larger population of both immature and committed myeloid cells.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study, we were interested in the better molecular understanding of a clinical homogenous subgroup with a poor prognosis (AML with monosomy 7 or deletion 7q (À7/del7q)). [5][6][7][8] We analyzed samples from AML patients with À7/del7q, AML patients with normal karyotype (without FLT3 mutation) and normal bone marrow stem cells of healthy individuals, by gene expression profiling. Comparison of these three groups showed that the expression of SKI, a nuclear co-repressor of the HDAC complex, is highly upregulated in À7/del7q AML.…”
Section: Introductionmentioning
confidence: 99%